Crowdfunding sebagai Alternatif Pembiayaan Pendidikan di Indonesia: Analisis dan Rekomendasi - Pasadani, Novi Wulandari Wahyu; Rusdiana, Rina (MES Management Journal, 2024)
Education is an important aspect of Indonesia's development, but the high expense of education frequently makes it difficult for people to obtain a decent education The Indonesian government has allocated a significant education budget, but it is still insufficient to meet the educational demands Crowdfunding is one of the solution to the education finance shortage that takes a modern and innovative approach. This study will analyze crowdfunding as an alternative to education financing, as well as make recommendations to parties interested in using crowdfunding in educational sectors.